The theoretical substantiation of fitness trainer's qualifying characteristics - M.V. Dutchak; M. N. Vasilenko (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
The necessity of addition to the existing profile of professions of qualifying characteristics fitness trainer is grounded. The analysis of Ukrainian and foreign scientists' publications was made. Those publications demonstrates the contradictory tendencies of becoming health fitness and training system of relevant personnel. Specificity of fitness trainer's work in various countries was revealed. It is proved that the fitness trainer should have knowledge of a wide range of issues: social, political, biological, medical, psychological, pedagogical, sports et al. The problem of the fitness trainers' distribution on the skill's levels was discussed. The following categories were proposed: fitness trainer and personal fitness trainer. Qualifying characteristics of the profession "fitness trainer" were designed. Grounded qualifying description fitness-trainer with presentation of sections: «task and duties», «must know», «qualifying requirements».